2021
DOI: 10.1177/11206721211054967
|View full text |Cite
|
Sign up to set email alerts
|

Bruch's membrane opening – minimum rim width measurement after acute primary angle-closure

Abstract: Purpose To evaluate Bruch's membrane opening – minimum rim width (BMO-MRW) and peripapillary retinal nerve fiber layer thickness (RNFLT) following an acute primary angle-closure attack (APAC). Materials and methods Nine consecutive patients with unilateral APAC were included. Patients with a bilateral attack, with signs of glaucomatous optic nerve damage or evidence of a previous APAC in either eye were excluded. Three months after the attack, all eyes underwent BMO-MRW and RNFLT measurements with SDOCT. APAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This may be related with the findings of a study by Chauhan et al [ 19 ], who stated that BMO-MRW may be more sensitive to ONH conformational changes that precede but do not directly correlate to RNFL loss. Some studies have shown that acute increases in IOP cause significant changes in BMO-MRW [ 50 , 51 ], and it has also been suggested that glaucoma subjects are more susceptible to these IOP increases compared to normal subjects [ 52 ]. In spite of the intraoperative IOP increases that occur during CCS and FLACS, in the present study, there was not a decrease in BMO-MRW following cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related with the findings of a study by Chauhan et al [ 19 ], who stated that BMO-MRW may be more sensitive to ONH conformational changes that precede but do not directly correlate to RNFL loss. Some studies have shown that acute increases in IOP cause significant changes in BMO-MRW [ 50 , 51 ], and it has also been suggested that glaucoma subjects are more susceptible to these IOP increases compared to normal subjects [ 52 ]. In spite of the intraoperative IOP increases that occur during CCS and FLACS, in the present study, there was not a decrease in BMO-MRW following cataract surgery.…”
Section: Discussionmentioning
confidence: 99%